2004
DOI: 10.1023/b:gerg.0000035955.07614.0d
|View full text |Cite
|
Sign up to set email alerts
|

Q-Stars in Anti de Sitter Spacetime

Abstract: We study q-stars with various symmetries in anti de Sitter spacetime in 3 + 1 dimensions. Comparing with the case of flat spacetime, we find that the value of the field at the center of the soliton is larger when the other parameters show a more complicated behavior. We also investigate their phase space when the symmetry is local and the effect of the charge to its stability.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This is amply supported by the studies on AdS/CFT correspondence [19,20]. Not only that, Astefanesei and Radu [21], and others [22,23,24,25,26], have shown that such studies also remain meaningful even in the presence of a negative cosmological constant.…”
mentioning
confidence: 72%
“…This is amply supported by the studies on AdS/CFT correspondence [19,20]. Not only that, Astefanesei and Radu [21], and others [22,23,24,25,26], have shown that such studies also remain meaningful even in the presence of a negative cosmological constant.…”
mentioning
confidence: 72%
“…Boson stars and boson shells representing the localized self-gravitating solutions were introduced long ago [1-3] and they have been studied vary widely in the literature . Such theories are being considered in the presence of positive [14][15][16][17] as well as negative [15,[17][18][19][20][21] values of the cosmological constant Λ. The theories with positive values of Λ (corresponding to the de Sitter (dS) space) are relevant from observational point of view as they describe a more realistic description of the compact stars in the universe since all the observations seem to indicate the existence of a positive cosmological constant.…”
Section: Introductionmentioning
confidence: 99%
“…We present a detailed discussion of the various regions in our phase diagram with respect to four bifurcation points. Our theory is seen to have rich physics in a particular domain for positive values of Λ which is consistent with the accelerated expansion of the universe.Introduced long ago [1-3], boson stars represent localized self-gravitating solutions studied vary widely in the literature [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Such theories are being considered in the presence of positive [14-16] as well as negative [17][18][19][20] values of the cosmological constant Λ.…”
mentioning
confidence: 99%